Petrology of lamprophyric in northern Jirandeh, Iran (Nexo Revista Científica, 2021)
This study was performed on the outcrops of lamprophyric lavas found in the north of Jirandeh and east of Lushan in the mountain of Alborz (north of Iran). These lavas has been placed discordantly on the middle Eocene lime..Petrographic observation indicates olivine phenocrysts, green-core alkaline clinopyroxenes, nepheline, abundant biotite, and apatites with flakes. and in the matrix it also contains biotite, olivine, clinopyroxene and plagioclase.The presence of carbonates, plagioclase and xenocrystals with rounded margins asserts the contamination with continental crust Petrologically, these rocks classify as alkaline lamprophyres of comptonite variety.These rocks can be subsumed under alkaline sodic categories at K2O/Na2O